2004
DOI: 10.1161/01.cir.0000118472.77237.fa
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Cause-Specific Mortality in the Atrial Fibrillation Follow-up Investigation of Rhythm Management (AFFIRM) Study

Abstract: the AFFIRM Investigators* Background-Expectations that reestablishing and maintaining sinus rhythm in patients with atrial fibrillation might improve survival were disproved in the Atrial Fibrillation Follow-up Investigation of Rhythm Management (AFFIRM) study. This report describes the cause-specific modes of death in the AFFIRM treatment groups. Methods and Results-All deaths in patients enrolled in AFFIRM underwent blinded review by the AFFIRM Events Committee, and a mode of death was assigned. In AFFIRM, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
112
2
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(124 citation statements)
references
References 32 publications
5
112
2
5
Order By: Relevance
“…Analyzing the results by use of a statistical model that treats the presence or absence of SR as a separate factor may remove this beneficial part of the AAD profile, allowing the detrimental effects to be expressed. The finding in the AFFIRM Study that the risk of noncardiac death was higher in the rhythm-control arm 11 could be explained by noncardiac adverse effects of AADs. It is also possible that the observed outcome was a result of biases in the model that were not identified.…”
Section: Epstein Et Al Effects Of Rhythm and Drugs In Affirmmentioning
confidence: 97%
“…Analyzing the results by use of a statistical model that treats the presence or absence of SR as a separate factor may remove this beneficial part of the AAD profile, allowing the detrimental effects to be expressed. The finding in the AFFIRM Study that the risk of noncardiac death was higher in the rhythm-control arm 11 could be explained by noncardiac adverse effects of AADs. It is also possible that the observed outcome was a result of biases in the model that were not identified.…”
Section: Epstein Et Al Effects Of Rhythm and Drugs In Affirmmentioning
confidence: 97%
“…In this regard, the potential for amiodarone to cause pulmonary toxicity may have been a factor in the significantly higher noncardiovascular death rate (including pulmonary deaths) reported for the rhythm-control arm of the AFFIRM study. 31 Although only 3 of the 169 noncardiovascular deaths in this group were considered related to amiodarone pulmonary toxicity, it is believed that other pulmonary deaths (n = 36) might have been caused by less-recognizable forms of amiodarone toxicity.…”
Section: Maintenance Of Sinus Rhythmmentioning
confidence: 98%
“…In the Atrial Fibrillation Follow-Up Investigation of Rhythm Management (AFFIRM) study (N = 4060), the absence of a greater benefit with rhythm control relative to rate control in the primary analysis was attributed to the incomplete suppression of AF and/or the negative impact of cardiac and noncardiac side effects of antiarrhythmic therapies. 30,31 Moreover, it was suggested that older patients had poorer outcomes on rhythm control because they may have been more vulnerable to drug toxicities than younger patients. Similarly, the lack of significant mortality benefits in other studies (eg, the Polish How to Treat Chronic Atrial Fibrillation [HOT CAFÉ; N = 205] and Rate Control vs Electrical Cardioversion [RACE; N = 522] studies) was attributed, at least in part, to drug toxicity.…”
Section: Mechanisms Of Af Development and Progressionmentioning
confidence: 99%
“…It is also not clear that safety of a drug in high-risk groups, eg, those with extensive heart disease, such as previous myocardial infarction and congestive heart failure, translates into safety in patient groups with AF that more commonly experience different modes of death. 45 An emerging story in the management of AF is the increasing importance of modulating factors. In this regard, we need to broaden our concept of what constitutes "antiarrhythmia" therapy in case of AF.…”
Section: The Futurementioning
confidence: 99%